Medical Imaging 2023: Image-Guided Procedures, Robotic Interventions, and Modeling 2023
DOI: 10.1117/12.2652980
|View full text |Cite
|
Sign up to set email alerts
|

Revealing pelvic structures in the presence of metal hip prostheses via non-circular CBCT orbits

Abstract: As the expansion of Cone Beam CT (CBCT) to new interventional procedures continues, the burdensome challenge of metal artifacts remains. Photon starvation and beam hardening from metallic implants and surgical tools in the f ield of view can result in the anatomy of interest being partially or fully obscured by imaging artifacts. Leveraging the flexibility of modern robotic CBCT imaging systems, implementing non-circular orbits designed for reducing metal artifacts by ensuring data-completeness during acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Task‐based noncircular trajectories were also explored to eliminate the influence of CB artifacts, 15–17 with parameterized trajectories based on information on patient and metal implants to reduce metal and CB artifacts. Many other non‐circular trajectories were also proposed, for example, sinusoidal trajectory, 18–20 helical trajectory, 21–23 circle‐and‐line trajectory 24 and circle‐and‐arc trajectory 25 …”
Section: Introductionmentioning
confidence: 99%
“…Task‐based noncircular trajectories were also explored to eliminate the influence of CB artifacts, 15–17 with parameterized trajectories based on information on patient and metal implants to reduce metal and CB artifacts. Many other non‐circular trajectories were also proposed, for example, sinusoidal trajectory, 18–20 helical trajectory, 21–23 circle‐and‐line trajectory 24 and circle‐and‐arc trajectory 25 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In recent years, non-circular scan orbits have been increasingly investigated for potential benefits such as increased field of view (FOV), [9][10][11][12] improved image quality and/or dose reduction, 7,[12][13][14][15] collision avoidance, 14,16 accom-modating upright patient positions [17][18][19] and reduced metal artifacts. 10,[20][21][22][23][24][25][26][27][28] While studies have demonstrated sufficient reproducibility for standard circular scanning orbits, [29][30][31][32] current implementations of non-circular orbits often result in a less predictable geometry due to factors such as gantry jitters, sagging, and manual data acquisition, and so forth. 8,12,[24][25][26][27]33,34 Since an accurate CBCT geometry is critical for the image quality of 3D reconstructions, we require a geometric calibration method that can address these challenges in practical implementations of non-circular or...…”
Section: Introductionmentioning
confidence: 99%